Achieving Cost Savings in Lithos Handling Through Pareto Principle and Class-Based Layout - Yaneke Laulu; Andian Ari Istiningrum; Fauzan Galank Sangadji; Rendy Bagus Pratama; Nur Ardiansah (Poltanesa, 2025)
Given the intense competition in today's industry, efficient warehouse management is crucial for enhancing operational performance. One key indicator of warehouse efficiency is the minimization of material handling equipment travel distance from the in/out points to the storage location, as well as the reduction in material handling costs. In this context, this research aimed to design a warehouse layout for lithos to optimize warehouse utilization by minimizing travel distance and material handling costs. To achieve this, the Class-based Storage method and Pareto Principle were employed, which groups items based on their movement characteristics and access frequency, allowing optimal placement while reducing travel distance and retrieval costs. The research results demonstrated that the implementation of the Class-based Storage with Pareto Principle in the lithos warehouse reduces the travel distance of forklifts from the storage rack to the in/out points by 6,760,470 meters, representing a 19% deviation compared to the existing layout. This reduction in travel distance contributes to a decrease in material handling costs by Rp 1,820,306.- per year.